EMOTION CONTROL IN THE QUR’AN: STUDY OF TOSHIHIKO IZUTSU’S SEMANTIC APPROACH TO KAẒIM VERSES - Hardivizon, Hardivizon; Mufidah, Mufidah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
One of the problems that always exists in every human being is negative emotions. This study aims to find out how to control emotions in the Qur’an through deepening the meaning of the word kaẓim with the sematic approach of Thosihiko Izutsu. This term is repeated 6 times which is covered in 6 surahs. Each verse contained in various surahs certainly has a different meaning, so it requires a deep understanding. The semantics of the Qur’an according to Izutsu is an attempt to reveal the world view (weltanschauung) through semantic analysis of the vocabulary or key terms of the Qur’an. The process carried out in this research is to examine the basic meaning, relational meaning, and historical meaning of the word kaẓim. The result of this research is that the word kaẓim based on the semantic analysis of Toshihiko Izutsu is a word that contains full meaning and closes it tightly. Signaling unfriendly feelings in one’s heart either because of anger, sadness, disappointment, shame, fear, and irritation, his mind is always demanding revenge, but he holds those feelings in his heart. Therefore, there are 4 ways to control emotions in kaẓim terms, namely, with prayer, dzikrullah, patient, and silence.